Acute Low-Tone Sensorineural Hearing Loss Presenting With Non-Rotatory Vestibular Prodrome in a High-Risk Patient: A Comprehensive Case Report on Aggressive Systemic Corticosteroid Management and Prognostic Evaluation - Marsella Lulu Aulia; Gustav Syukrinto (CV. Publikasi Indonesia, 2026)
Acute Low-Tone Hearing Loss (ALHL) is often recognized as the clinical manifestation of cochlear-restricted endolymphatic hydrops (EH), making it highly prone to recurrence and subsequent conversion into definitive Menière's Disease (MD). Given this risk, necessitate immediate and aggressive therapeutic intervention to stabilize inner ear function. This research aims to study the therapy and observation in patients with ALHL. Case Report A 27-year-old female presented with acute unilateral tinnitus, aural fullness and new-onset subtle, non-rotatory dizziness, unsteadiness and an episode of nausea and vomiting. Pure tone audiometry, showed a low tone sensorineural hearing loss. What do we have to consider in treatment of patient with ALHL to avoid worsening progression and achieve complete recovery? Literature research was carried out through PubMed and Google Scholar with keywords